PENGARUH MODAL KERJA DAN TENAGA KERJA TERHADAP PENDAPATAN USAHAMIKRO KECIL MENENGAH REBANA DI KECAMATAN BUNGAH KABUPATEN GRESIK - Ayu Dwi Lestari (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2017)
The purpose of this research is to identify the variables that affect the income of craftmen rebana District Bungah Gresik. This researhc used 36 respondent assample, Primer data were used in this research.. This research tested two independent variables, namely capital and labor that affect the dependent variable is income. The purpose of this research is also to find out the effect of working capital, and labor to earnings by using multiple linear regression analysis. The resultsof thr research showed that the variables significantly influence the working capital income, while labor not significant effect on income.